2017
DOI: 10.3389/fpsyg.2017.00729
|View full text |Cite
|
Sign up to set email alerts
|

Can Leader–Member Exchange Contribute to Safety Performance in An Italian Warehouse?

Abstract: Introduction: The research considers safety climate in a warehouse and wants to analyze the Leader–Member Exchange (LMX) role in respect to safety performance. Griffin and Neal’s safety model was adopted and Leader-Member Exchange was inserted as moderator in the relationships between safety climate and proximal antecedents (motivation and knowledge) of safety performance constructs (compliance and participation).Materials and Methods: Survey data were collected from a sample of 133 full-time employees in an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Past research has examined employees' behavior predicted by several factors, such as the creation of a positive organizational climate to stimulate safe work behavior in employees (Smith-Crowe et al, 2003). Employees' behavior, including OCB, was positively affected by the ethical climate through the social identity approach (Pagliaro et al, 2018).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Past research has examined employees' behavior predicted by several factors, such as the creation of a positive organizational climate to stimulate safe work behavior in employees (Smith-Crowe et al, 2003). Employees' behavior, including OCB, was positively affected by the ethical climate through the social identity approach (Pagliaro et al, 2018).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Two important antecedents at a more distal level include supervisor safety climate at the team level and organizational support for safety participation at the higher company level. On the one hand, a supervisor safety climate is considered essential by scholars (Zohar, 2008) to communicate the priority of safety management instances and values in the daily working activities in the organization at the shop floor level (Mariani, Curcuruto, Matic, Sciacovelli, & Toderi, 2017). On the other hand, organizational support for safety participation concerns the degree whereby companies set up effective managerial systems and practices which sustain open safety communication between the workforce and their organizations (Tucker et al, 2008).…”
Section: Antecedents Of Safety Citizenshipmentioning
confidence: 99%
“…Hofmann and Morgeson (1999) established link between leader-member exchange (LMX) and perceived organizational support (POS) with safety-related outcomes: safety communication, safety commitment and accidents, which concluded that LMX was significantly related with safety communication, safety commitment and accidents. LMX theory has widely been adopted to gain an insight on the job performance, work commitment, safety behavior, job satisfaction and turnover intentions (Mariani et al, 2017). Leader-member exchange (LMX) was explored to describe the quality of relationship between subordinates and leaders in the organizations.…”
Section: Safety Motivationmentioning
confidence: 99%